Utilization Of Artificial Intelligence In Image-Based Medical Diagnosis - Febriani, Rizki Annisa (LPPJPHKI Universitas Dehasen Bengkulu, 2023)
Artificial Intelligence (AI) has become one of the most revolutionary technologies in the medical field, especially in image-based diagnostics. This research aims to explore the utilization of AI, particularly through deep learning and Convolutional Neural Networks (CNN), in improving the accuracy and efficiency of medical diagnosis systems. This research uses a literature study approach and prototype implementation to analyze how AI can support doctors in making faster and more informed clinical decisions. The results show that AI is able to improve the accuracy of diagnoses as well as reduce human errors in medical image analysis.